Peningkatan Kinerja Ruas Jalan Akibat Aktivitas Pasar dan Pedagang Pada Bahu Jalan (Studi Kasus: Jalan Benteng Pancasila, Kota Mojokerto) - Amalia Nur Adibah; Muhammad Adam Novan Ardiansyah; Andi Syaiful Amal; Alik Ansyori Alamsyah; Azhar Adi Darmawan (Universitas Batanghari Jambi, 2023)
Benteng Pancasila street often experiences congestion caused by excessive side barriers due to the large number of parked vehicles and vendors selling on the shoulder of the street. This study aims to improve Jl Benteng Pancasila section performance and forecasts for the next five years. This research is quantitative descriptive research that produces quantitative data and being analysis based on descriptive situation. This study shows that based on peak time and side resistance calculations, the final saturation (DS) value is 0.75 at LOS D. After implementing the improvement alternatives, the DS values are 0.71 for LOS C in 2022 and 0.82 in 2026. LOS value of D. This condition needs to alternative improvement to improve road performance Benteng Pancasila street.